Ketidakberagaman Pangan pada Anak Usia 6-23 Bulan dan Faktor yang Berhubungan di Provinsi Sulawesi Tengah Indonesia: Prevalence of Unmet Minimum Dietary Diversity and Associated Factor among Children Aged 6-23 Months in Central Sulawesi, Indonesia - Firlia Ayu Arini; Sugiatmi Sugiatmi; Nabilla Zalfa Azahra; Iin Fatmawati; Utami Wahyuningsih (Amerta Nutrition, 2025)
Background: Central Sulawesi recorded the highest prevalence of underweight in 2022. One-quarter of children were underweight in this province, which placed them at risk of stunting. Food diversity was a protective factor against stunting. Unmet Minimum Dietary Diversity (MDD) indicates inadequate feeding practices that contribute to undernutrition. Objectives: The purpose of this study was to determine the prevalence of unmet Minimum Dietary Diversity among children aged 6-23 months in Central Sulawesi and its determinants. Methods: This study analyzed secondary data from the Indonesian Nutritional Status Survey in 2022 with a total sample size of 2372 children. The outcome variable was Unmet Minimum Dietary Diversity, and the determinant variables were parental education, occupation, children's age group, and child sex. Multiple logistic regression was used to examine the association between the determinant variables and the outcome. Results: The prevalence of unmet MDD was 75.5%. Children in the age group of 6-11 months, having mothers with the lowest education level, having fathers with an unstable income, and male children were significant determinants of unmet MDD. Children in the age group 6-11 months had a 2.6 times greater risk of having unmet MDD, and it was the most dominant determinant for unmet MDD. Conclusions: This study demonstrated that unmet MDD was more prevalent among children at the beginning of the complementary feeding age. To reduce the risk of undernutrition, strengthened nutrition interventions should be given to improve feeding practices among children in the complementary feeding age.